Meningkatkan Antusiasme Anak-Anak Desa Naman Jahe dalam Belajar Mengaji melalui Pendekatan Ceria dan Interaktif - Andre, Muhammad; Arhan, Muhammad; Farhan, Muhammad; Wandari, Anisa; Syahputri, Feby; Mulyani, Marito; Pohan, Sakinah; Demayanti, Yuli; Johana, Florestina; Fadilla, Wafiq (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aimed to increase the enthusiasm of children in Naman Jahe Village for learning to recite the Qur’an through a joyful and interactive approach. Initial observations revealed that the Qur’an learning sessions at Masjid Raya Naman Jahe were monotonous and less engaging, highlighting the need for innovative teaching methods suited to the characteristics of early childhood learners. The method employed was Participatory Action Research (PAR), involving 13 students from various faculties of IAIN Lhokseumawe. The core program, Bimbel Ceria, was conducted over 40 days in 20 sessions, held every afternoon following Qur’an and Iqra’ lessons. The activities integrated general subjects such as mathematics and Arabic language with religious content using playful methods, quizzes, and ice-breaking games. Data were collected through direct observation, informal interviews, and activity documentation, and were analyzed thematically and narratively. The results showed an increase in children’s participation from 85% in the first week to 100% in the final week. Children demonstrated positive behavioral changes, such as arriving earlier, asking questions actively, and showing high learning motivation. Community response was overwhelmingly positive, with strong support from the mosque’s nazir and parents for the program’s continuation. The discussion indicates that the joyful and interactive approach effectively fosters learning motivation in early childhood, strengthens religious literacy, and positions the mosque as a community-based educational center. This program can be replicated in other villages with similar characteristics as a model for inclusive and engaging Islamic education.